2019
DOI: 10.2147/idr.s216926
|View full text |Cite
|
Sign up to set email alerts
|

<p>Distinct Antimicrobial Resistance Profiling Of Clinically Important <em>Aeromonas</em> Spp. In Southwest China: A Seven-Year Surveillance Study</p>

Abstract: BackgroundCo-evolution of host and aeromonads has diversified their spectrums of diseases and antibiograms, while a paucity of data was concerning about this diversity in China. To fill this gap, this study was aimed to investigate and compare antimicrobial resistance (AMR) patterns of clinically important Aeromonas spp. from various clinical sources.MethodsA multicenter retrospective surveillance study was conducted in Chongqing from 2011 to 2017. Data of strains were retrieved from the database of China Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…Moreover, Aeromonas salmonicida spp salmonicida is resistant to some β-lactam antibiotics such as Cefixime (CFM), Cefrtriaxone (CRO), Cefoxitin (FOX), Piperacillin (PRL), and the cephalosporin family (Table 4). This resistance is similar with the results of a study conducted by Valdes et al [2015)] and Yang et al [2019]. However, it is sensitive to Aminoside, Penicillin, Phenicole, Furoquinolonen, Macrolide, Fusidamine, Lincosamide, Quinolone, Rifamycin, Sulfamide, Cycline, Glycopeptide and other antibiotics from β-lactamine family as Cefalexin (CN), Cefotetan (CT), Cefotaxim (CTX), Imipenem (IPM).…”
Section: Assessment Of Antibiotic Resistancesupporting
confidence: 88%
“…Moreover, Aeromonas salmonicida spp salmonicida is resistant to some β-lactam antibiotics such as Cefixime (CFM), Cefrtriaxone (CRO), Cefoxitin (FOX), Piperacillin (PRL), and the cephalosporin family (Table 4). This resistance is similar with the results of a study conducted by Valdes et al [2015)] and Yang et al [2019]. However, it is sensitive to Aminoside, Penicillin, Phenicole, Furoquinolonen, Macrolide, Fusidamine, Lincosamide, Quinolone, Rifamycin, Sulfamide, Cycline, Glycopeptide and other antibiotics from β-lactamine family as Cefalexin (CN), Cefotetan (CT), Cefotaxim (CTX), Imipenem (IPM).…”
Section: Assessment Of Antibiotic Resistancesupporting
confidence: 88%
“…in Southwest China from 2011 to 2017. 26 And this report also mentioned that A. hydrophila has a resistance rates of 30.2% to ceftriaxone; 20% to ceftazidime, cefepime, aztreonam, and ciprofloxacin; and less than 10% to imipenem and meropenem. These findings suggest that the drug resistance of A. hydrophila is an increasingly serious problem in clinical infections.…”
Section: Discussionmentioning
confidence: 78%
“…A previous seven-year surveillance study demonstrated that A. hydrophila (65.6%, 745/1135) was the most predominant species from clinical Aeromonas spp. in Southwest China from 2011 to 2017 [21]. It also reported that A. hydrophila has a resistance rates of 30.2% to ceftriaxone, followed by 20% to ceftazidime, cefepime, aztreonam, and cipro oxacin, and less than 10% to imipenem and meropenem.…”
Section: Discussionmentioning
confidence: 97%